Respon Setek Cabang Bambu Betung (Dendrocalamus Asper) Akibat Pemberian Asam Indol Butirat (AIB) - Sari, Erviana; Indriyanto, Indriyanto; Bintoro, Afif (Jurnal Sylva Lestari, 2016)
Betung bamboo (Dendrocalamus asper) as multipurpose plant could be developed with vegetative and generative propagation. Branch cuttings was the easiest way in the betung bamboo vegetative propagation. One of plant growth regulators that could be used to spur betung bamboo branch cutting was indole butyric acid (IBA). This study was conducted to evaluate the betung bamboo branch cutting response from various concentration of IBA and to know the best concentration of IBA to spur the growth. The experiment was conducted in Palembang's Bamboo Plantation Collection and Development Research Institute of Forest areal, Tanjung Agung, District Tanjungan, South Lampung Regency, from March to June 2012. This research used Completely Randomized Design (CRD) with five treatments: IBA 0 ppm (control), 100 ppm, 200 ppm, 300 ppm, and 400 ppm of concentration. Each of experimental unit consisted of five cuttings with five replications. Percentage of life, length of shoot, number of shoot, number of leave, shoot's diameter, and root's length were the observed variables. The result showed that betung bamboo branch cuttings were responsive to IBA, and IBA 200 ppm concentration gave better results to the betung bamboo branch cuttings than IBA 0 ppm (control), 100 ppm, 300 ppm, and 400 ppm concentration. Based on this study, it was recomended to use 200 ppm of IBA for betung bamboo branch cutting. Keywords: betung bamboo, branch cutting, indole butyric acid